Imaging and Tracking Through Scattering Medium With Low Bit Depth Speckle - Qinghuan Xu; Baoqing Sun; Jia Zhao; Zuojia Wang; Liuge Du; Chonglei Sun; Xianye Li; Xun Li (IEEE Photonics Journal)
Optical imaging/tracking through scattering medium is a difficult challenge. We demonstrate a method using speckles with multiple bit depths to image objects through scattering medium. The image of the object can be reconstructed even if the speckles are binary. Speckles with different bit depths are obtained by quantifying the original speckle. And we discuss the application of binarized speckles in tracking moving object. The binarized speckles can be used to recover the track with high accuracy. The range of the object's motion can be much larger than the range of memory effect, as long as the object's size and the moving step are within the range of memory effect. Imaging and tracking with low bit depth have the potential to reduce the hardware requirements of camera and storage space of images.